Early diagenesis, sedimentary dynamics and metal enrichment reveal deep-sea ventilation in Magellan Seamounts during the middle Pleistocene - Shen, Zhongshan; Chen, Yanping; Mikhailik, Pavel; Cai, Yun; Wang, Haifeng; Yi, Liang (Frontiers in Marine Science, 2024)
Seamounts are ubiquitous topographic units in the global oceans, and the Caiwei Guyot in the Magellan Seamounts of the western Pacific is a prime example. In this study, we analyzed a well-dated sediment core using magnetic properties, sediment grain size, and metal enrichment to uncover regional ventilation history during the middle Pleistocene and explore potential linkages to global climate changes. Our principal findings are as follows: (1) The median grain size is 3.3 ± 0.2 μm, and clay and silt particles exhibit minimal variation, with average values of 52.8 ± 1.8% and 38.2 ± 1.6%, respectively, indicating a low-dynamic process; (2) Three grain-size components are identified, characterized by modal patterns of ~3 μm (major one), ~40 μm, and 400–500 μm, respectively; (3) Magnetic coercivity of the deep-sea sediments can be classified into three subgroups, and their coercivity values are 6.1 ± 0.5 mT, 25.7 ± 1.0 mT, and 65.2 ± 2.1 mT. Based on these results, we propose a close linkage between magnetic coercivity and metal enrichment, correlating with changes in deep-sea circulation intensity. Conversely, sediment grain-size changes seem to be more strongly influenced by eolian inputs. Consequently, we suggest that regional ventilation has weakened since ~430 ka, likely linked to a reduction in Antarctic bottom water formation.